2006
DOI: 10.14314/polimery.2006.027
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of aged composition of polyethylene with synthetic polyester

Abstract: Streszczenie-Zbadano wp³yw wstêpnego starzenia w warunkach abiotycznych (foto-, termo-i fototermodegradacja) na przebieg powodowanej przez grzyby mikroskopowe Penicillium funiculosum biodegradacji folii wykonanej z mieszaniny 80 % PE-LD i 20 % poliestru "Bionolle ® ". W celach porównawczych badano te¿ folie wykonane z czystych sk³adników tej mieszaniny. Stopieñ ka¿dego z badanych rodzajów degradacji oceniano na podstawie pomiarów ubytku masy folii, ich w³aoeciwooeci mechanicznych oraz morfologii powierzchni. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Some authors have demonstrated weight loss as an important biodeterioration variable. As a case in point, Łabużek et al, (2006) reported ˂0.04% weight loss in PE sheets after a 16 day photo-thermal degradation process (UV 250–400 nm and 50° C) [ 47 ]. Sheik et al (2015) observed LDPE sheet weight loss (0.3 mg) after they were exposed to gamma rays greater than 200 KGy and incubaed with fungi during 90 days [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated weight loss as an important biodeterioration variable. As a case in point, Łabużek et al, (2006) reported ˂0.04% weight loss in PE sheets after a 16 day photo-thermal degradation process (UV 250–400 nm and 50° C) [ 47 ]. Sheik et al (2015) observed LDPE sheet weight loss (0.3 mg) after they were exposed to gamma rays greater than 200 KGy and incubaed with fungi during 90 days [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Untreated films showed a lower number of adhered cells when compared to the treated films, showing that cell adhesion was influenced by the treatments, which increased the biocompatibility [ 16 ]. The synergetic effect of the abiotic and biotic process in the biodegradation of synthetic polymers was also studied and reviewed recently [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%